Infrasound Monitoring for Atmospheric Studies - Le Pichon, Alexis; Blanc, Elisabeth; Hauchecorne, Alain; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2009)
The infrasound field, the science of low-frequency acoustic waves, has developed into a broad interdisciplinary field encompassing academic disciplines of physics and recent technical and scientific developments. The infrasound network of the International Monitoring Network (IMS) of the CTBT-Organization has demonstrated its capability for detecting and locating infrasonic sources such as meteorites, volcanic eruptions, earthquakes, auroras, mountain associated waves... Nearly 70% of the global network is now operational and regional cluster arrays are deployed around the globe. Systematic investigations into low-frequency acoustic signals have evidenced an unprecedented potential of the monitoring of infrasonic waves permanently generated by natural and man-made events. Furthermore, recent studies point out new insights on quantitative relationships between observables and atmospheric specifications, and therefore opening new fields into the mathematics of geophysical inverse problems for atmospheric remote sensing. This volume reviews the most important areas of infrasound, with emphasis on the latest researches and applications, e.g. instrumentation, engineering, signal processing, source monitoring, propagation modeling, atmospheric dynamics, global changes, remote sensing methods. Researchers and students will benefit from a comprehensive content of infrasound related topics, where both fundamental and applied topics are discussed by authors from international institutions, all experts in their fields.
HISTORY, INSTRUMENTATION, NETWORK -- The Characteristics of Infrasound, its Propagation and Some Early History -- The IMS Infrasound Network: Design and Establishment of Infrasound Stations -- Monitoring the Earth$1 (Bs Atmosphere with the Global IMS Infrasound Network -- Low-Noise Broadband Microbarometers -- A Review of Wind-Noise Reduction Methodologies -- SOURCES, OBSERVATIONS, AND PROPAGATION -- Worldwide Observations of Infrasonic Waves -- Infrasonic Observations of Open Ocean Swells in the Pacific: Deciphering the Song of the Sea -- Generation of Microbaroms by Deep-Ocean Hurricanes -- Acoustic-Gravity Waves from Earthquake Sources -- Seismic Waves from Atmospheric Sources and Atmospheric/Ionospheric Signatures of Seismic Waves -- Acoustic-Gravity Waves from Impulsive Sources in the Atmosphere -- Meteor Generated Infrasound: Theory and Observation -- High-latitude Observations of Infrasound from Alaska and Antarctica: Mountain Associated Waves and Geomagnetic/Auroral Infrasonic Signals -- Some Atmospheric Effects on Infrasound Signal Amplitudes -- Atmospheric Variability and Infrasound Monitoring -- PROPAGATION MODELING IN A REALISTIC ATMOSPHERE -- On the Prospects for Acoustic Sounding of the Fine Structure of the Middle Atmosphere -- Numerical Methods to Model Infrasonic Propagation Through Realistic Specifications of the Atmosphere -- Misty Picture: A Unique Experiment for the Interpretation of the Infrasound Propagation from Large Explosive Sources -- Ground Truth Events: Assessing the Capability of Infrasound Networks Using High Resolution Data Analyses -- ATMOSPHERIC INVESTIGATIONS FROM GLOBAL CONTINUOUS INFRASOUND MONITORING -- Contribution of Infrasound Monitoring for Atmospheric Remote Sensing -- Global Scale Monitoring of Acoustic and Gravity Waves for the Study of the Atmospheric Dynamics -- Dynamics and Transport in the Middle Atmosphere Using Remote Sensing Techniques from Ground and Space -- The Representation of Gravity Waves in Atmospheric General Circulation Models (GCMs) -- Inversion of Infrasound Signals for Passive Atmospheric Remote Sensing.s
Keywords: Earth sciences; Geotechnical engineering; Acoustics; Physical measurements; Measurement; Noise control; Earth Sciences; Geotechnical Engineering & Applied Earth Sciences; Acoustics; Environmental Monitoring/Analysis.; Measurement Science and Instrumentation; Noise Control; Electronic books